Numerical verification of geotechnical structure in unfavourable geological conditions – case study - Drusa, Marian (GeoScience Engineering, 2015)
Numerical modelling represents a powerful tool not only for special geotechnical calculations in cases of complicated and difficult structure design or their foundation conditions, but also for regular tasks of structure foundation. Finite element method is the most utilized method of numerical modelling. This method was used for calculations of the retaining wall monitored during 5 years after construction. Retaining wall of the parking lot with the facing from gabion blocks was chosen for numerical model. Besides the unfavourable geological conditions, a soft nature of the facing was also a difficult part of the modelling. This paper presents the results of the modelling when exact geometry, material characteristics and construction stages were simulated. The results capture the trend of displacements even though the basic material models were utilized. The modelling proved the ability of the finite element method to model the retaining structure with sufficient accuracy as well as reasonable demand on quality and quantity of input data. This method can then be used as a regular design tool during project preparation.